Suggestion of Spongia (Heterofibria) peddemorsi as replacement name for Spongia (Heterofibria) cooki Samaai, Pillay & Janson, 2019 - Samaai, Toufiek; Pillay, Ruwen; Janson, Liesl (Zootaxa, 2020)
Rob Van Soest (pers. communication) remarked that Spongia (Heterofibria) cooki Samaai, Pillay & Janson, 2019 is a junior primary homonym of Spongia vermiculata cookii Hyatt, 1877, now accepted as Spongia (Spongia) cookii Hyatt, 1877. Following the ICZN (art. 57.2, art. 58.14 [regarding -ii and -i], ICZN 1999) the published species name (Samaai et al. 2019) is unavailable and we now suggest replacing the name with Spongia (Heterofibria) peddemorsi following art. 60, ICZN (1999). The holotype is deposited into the collection at the Iziko South African Museum, Cape Town, SAM-A24791, for further collection data see Samaai et al. 2019.